A scholarly contribution to educational praxis - Oosthuizen, Izak; Mokoena, M. A. (AOSIS, 2016)
This publication contains original research targeting scientific specialists in the field of education. Not only is the disposition of its research endeavours grounded on a philosophical basis, it is also embedded in the empirical. The research methodology of each chapter emanates from applicable philosophical assumptions in the form of an applicable theoretical and conceptual framework. The latter forms a firm basis for the application of sound empiricism. Both qualitative and quantitative empirical approaches were alternatively applied in the various chapters. The content of each chapter was meticulously analysed before being finally accepted. In response to the call for chapters, 26 abstracts were received. After evaluation of these abstracts, 24 authors were granted the opportunity of submitting full manuscripts for evaluation. Subsequently the latter were submitted to a rigorous double-blind peer review process. These manuscripts were submitted to at least two or three specialist reviewers in their particular fields of specialisation. All of these review reports are preserved and kept for enquiry and assessment. The content of the current book was chosen from a selection for a 2014 publication which did not obtain a subsidy from the DHET, titled Nuances of Teaching Learning and Research, published by AndCork Publishers. After careful re-evaluation, a much smaller number of chapters was selected, substantially reworked and considerably extended, after which the chapters were again submitted to a double-blind peer review process. Ultimately, of the 26 abstracts originally received only 10 were finally accepted as suitable for publication in the current volume. Finally, in terms of the requirements set by clause 6.12 of the Department of Higher Education and Training policy on reworked publications, this book now contains more than 50% original content not published before. The content of this book adds to the body of scholarly knowledge in education. In his evaluation of the book, Acting Executive Dean, Faculty of Education and Training, Professor Akpovire Oduaran, made the following remarks: To a large extent, the ideas put together in this book have come from data generated not just from literature found in books and journals but actual interactions with educators and the learning environment. So then, what the reader is offered in this volume is the articulation of ideas that have been interrogated, structured and presented in surprisingly simplistic and yet incisive and academically enriching content that can match the standards of scholarship that is available in the Western World. Yet, what makes this book so welcome, relevant and timely, is the fact that it is built around Afrocentric theories and practices such as one may find in imported literature.